ANALISIS SEMIOTIKA IKLAN LAYANAN KELUARGA BERENCANA (KB) VERSI PERNIKAHAN DINI - Suryani Suryani; Suraili Suraili (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
Family Planning (KB) is one of the government programs aimed at limiting the number of children in a family and inhibiting the rate of population growth in Indonesia. To introduce the program, the government made an advertisement for KB service version of Early Marriage on television. These ads contain meanings that are indirectly conveyed through the symbols in the ad. The ad will be analyzed using Jurgen Ruesch's semiotic analysis model, classifying all verbal and nonverbal cues in sign language, action language and object language. The meaning of the symbol consisting of the language of the sign, the language of action and the language of the object that includes body communication such as gestures, facial communication, eyes and touch as well as space and time communication in the KB ad version of early marriage sends the message that early marriage is better avoided for the maturity and readiness of the couple in the household both mentally and physically.